Estimation of overall heat transfer coefficients in packed beds with cocurrent downflow of gas and liquid - Taulamet, María José (2014)
This contribution undertakes the analysis of heat transfer between a packed bed with cocurrent downflow of gas and liquid, widely known as trickle bed reactor, and an external heating or cooling fluid. Experiments were carried out in a bench scale reactor with water and air, covering trickle and pulsing regimes, in beds presenting aspect ratios (tube to particle diameter ratio) from 4.7 to 34. Four sizes of glass spheres, two of glass cylinders, a mixture of spheres and a commercial trilobe pellet were employed as particles. With the purpose of estimating the overall heat transfer rates, a 1D pseudo-homogeneous model with a single parameter (overall bed heat transfer coefficient, hT) was employed to analyze the experimental results. An expression to estimate hT (expressed as Nusselt number) for the low interaction regime in terms of liquid Reynolds number, a pellet shape factor and bed to particle diameter ratio is proposed. This expression approximates the experimental values with an average deviation of around 10%.